2018
DOI: 10.1002/hep.29628
|View full text |Cite
|
Sign up to set email alerts
|

A risk score to predict the development of hepatic encephalopathy in a population‐based cohort of patients with cirrhosis

Abstract: Patients with cirrhosis can be stratified by a simple risk score for HE that accounts for changing clinical data; our data also highlight a role for statins in reducing cirrhosis complications including HE. (Hepatology 2017).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
78
0
3

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 76 publications
(84 citation statements)
references
References 41 publications
3
78
0
3
Order By: Relevance
“…For instance, it may be that opioid‐induced altered mental status is being misdiagnosed as HE. However, the annual incidence of HE and other decompensation events are comparable to what has been published in the literature, providing external validity to our results . In addition, any event prompting a billing code for HE or the initiation of lactulose/rifaximin is likely to be clinically important.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…For instance, it may be that opioid‐induced altered mental status is being misdiagnosed as HE. However, the annual incidence of HE and other decompensation events are comparable to what has been published in the literature, providing external validity to our results . In addition, any event prompting a billing code for HE or the initiation of lactulose/rifaximin is likely to be clinically important.…”
Section: Discussionsupporting
confidence: 85%
“…In fact, one single‐centre study reported that an opioid prescription at discharge increased overall readmissions, but not hepatic encephalopathy‐related readmissions over 6 months . Furthermore, in a longitudinal cohort of United States veterans, baseline opioid use was not found to be an independent predictor of hepatic encephalopathy …”
Section: Introductionmentioning
confidence: 99%
“…For patients with nonalcoholic nonviral cirrhosis, the incidence rate of HE was lower than for other causes of cirrhosis. Data on the prediction of decompensation and HE have been drawn from younger (<60 years old) cohorts of patients with predominantly HCV or alcohol‐related cirrhosis . However, many, perhaps most, new diagnoses of cirrhosis in the United States are related to NAFLD .…”
Section: Discussionmentioning
confidence: 99%
“…One example is the model proposed by Riggio et al, who developed and validated a risk score to identify patients with cirrhosis at 1‐year risk for overt HE based on previous HE and albumin levels . Tapper et al developed a score to stratify the HE risk according to the presence of some clinical variables (laboratory tests and drugs), such as bilirubin, albumin as well as statins and non‐selective betablockers use . However, this simple risk score showed some concerns, beyond of being a retrospective study, such as the lack of some essential information (ie, previous HE episodes) or the use of inadequate statistical methods (ie, Cox regression analysis) .…”
Section: Discussionmentioning
confidence: 99%